Legal Assitance and Legal Literacy Enhancement for Victims of Termination of Employment in Efforts to Expand Access to Justice - Irene Mariane; Henny Saida Flora; Suryani Intan Pratiwi Puwa; Asnal Hafiz; Dwi Nurahman (PT Inovasi Pratama Internasional, 2026)
Termination of Employment (PHK) in Indonesia has escalated significantly, with over 88,519 cases recorded in 2025 alone, yet many victims remain unaware of their legal rights and are unable to navigate complex dispute resolution mechanisms. This study examines the role of legal assistance programs and legal literacy enhancement initiatives in expanding access to justice for PHK victims within a specific Indonesian district. Employing a qualitative socio-legal research methodology, this study conducted in-depth interviews with twenty-five (25) PHK victims, ten (10) legal aid providers, five (5) government officials from the local Manpower Office, and three (3) trade union representatives, complemented by document analysis and observation of mediation proceedings. The findings reveal that a significant majority of PHK victims (84%) possessed low to moderate levels of legal literacy regarding their statutory entitlements, including severance pay (pesangon), long-service awards (UPMK), and compensation for rights (UPH). Furthermore, 92% of respondents encountered substantial barriers to accessing justice, including prohibitive legal costs, procedural complexity, and geographic isolation from Industrial Relations Courts. Legal assistance provided by Legal Aid Institutions (LBH) and university legal clinics demonstrably improved the likelihood of PHK victims securing their rights, with assisted victims being 3.2 times more likely to obtain a favorable settlement or court ruling. However, the study also identifies critical challenges, including the limited capacity of legal aid organizations and persistent issues of weak law enforcement against recalcitrant employers. The research concludes that a synergistic approach, combining the provision of pro bono legal assistance with targeted community-based legal literacy programs, is essential for addressing the justice gap experienced by PHK victims. The study recommends the formal establishment of a District-Level Legal Aid Task Force for Employment Disputes and the integration of labor rights education into local community development programs.